Tabu-Genetic Algorithm-Based Model for Poultry Feed Formulation - Adebayo, Oluwadare Samuel; Junior, Gabriel Arome; Grace, Ogunrinde Oluwakemi (International Journal of Sustainable Agricultural Research, 2019)
Poultry feed cost represents a significant part of operational cost of poultry production. Consequently, efficient feed formulation practice is required for a sustainable poultry production. Many poultry farmers, employ inefficient methods like rule of thumb and intuition to handle feed formulation problem. This paper presents the report of the development of a feed formulation model which can be used to harness the potentials of locally available feed stuffs toward producing a balanced poultry feed. To achieve this aim, a hybrid Tabu-Genetic Algorithm Model ((TAM) was developed for layers mash feed formulation as case study. Thirteen (13) decision variables and eight (8) constraints were identified and used in the research. Secondary data were collected from the recommended nutrient requirements schedule made available by both the Ondo State Ministry of Agriculture and the Freedom Feed Mill (a local feed miller) in Akure, South-West Nigeria. Based on this data, the optimal solution of the TAM developed for the layers mash produced a balanced feed at reduced cost.